Dialysis Treatment Is an Independent Risk Factor for Foot Ulceration in Patients With Diabetes and Stage 4 or 5 Chronic Kidney Disease - Ndip, Agbor (American Diabetes Association, 2010)
OBJECTIVE: To determine whether dialysis treatment is an independent risk factor for foot ulceration in patients with diabetes and renal impairment. RESEARCH DESIGN AND METHODS: We performed a cross-sectional study of consecutive patients with diabetes and stage 4 or 5 chronic kidney disease (CKD) attending clinics in Manchester (U.K.). Patients were classified as either receiving dialysis therapy (dialysis) or not (no dialysis). Foot assessment included diabetic peripheral neuropathy (DPN), peripheral arterial disease (PAD), prior foot ulceration and amputation, and foot self-care. Risk factors for prevalent foot ulceration were assessed by logistic regression. RESULTS: We studied 326 patients with diabetes and CKD (mean age 64 years; 61% male; 78% type 2 diabetes; 11% prevalent foot ulceration). Compared with no dialysis patients, dialysis patients had a higher prevalence of DPN (79 vs. 65%), PAD (64 vs. 43%), prior amputations (15 vs. 6.4%), prior foot ulceration (32 vs. 20%), and prevalent foot ulceration (21 vs. 5%, all P < 0.05). In univariate analyses, foot ulceration was related to wearing bespoke footwear (odds ratio 5.6 [95% CI 2.5–13]) dialysis treatment (5.1 [2.3–11]), prior foot ulceration (4.8 [2.3–9.8], PAD (2.8 [1.3–6.0], and years of diabetes (1.0 [1.0–1.1], all P < 0.01). In multivariate logistic regression, only dialysis treatment (4.2 [1.7–10], P = 0.002) and prior foot ulceration (3.1 [1.3–7.1], P = 0.008) were associated with prevalent foot ulceration. CONCLUSIONS: Dialysis treatment was independently associated with foot ulceration. Guidelines should highlight dialysis as an important risk factor for foot ulceration requiring intensive foot care.